Halo Scalp Ring: An Annular Alopecia Associated with Birth Injury - Shin, Jun-Oh; Roh, Dongyoung; Son, Jin-Hwa; Shin, Kihyuk; Kim, Hoon-Soo; Kim, Byung-Soo; Kim, Moon-Bum; Ko, Hyun-Chang (Annals of dermatology, 2023)
KCI Citation Count: 0